The Effects of Fear of Missing Out and Hedonic Shopping Motivation on Post-Purchase Dissonance: The Mediating Role of Impulse Buying among Generation Z TikTok Shop Users in Indonesia - Alimin Hendra; Johan Adijaya (PT. Mawadaku Sukses Solusindo, 2026)
The rapid growth of social commerce has fundamentally transformed consumer purchasing behavior, particularly among Generation Z, who are highly engaged with digital platforms. As one of the leading video-based social commerce platforms, TikTok Shop integrates entertainment, interactive content, and real-time promotional activities that encourage impulsive purchasing behavior. However, the increasing prevalence of impulsive purchases has also raised concerns regarding post-purchase dissonance, a psychological condition characterized by feelings of doubt, discomfort, or regret following a purchase. This study aims to examine the effects of Fear of Missing Out (FOMO) and Hedonic Shopping Motivation on Post-Purchase Dissonance, with Impulse Buying serving as a mediating variable among Generation Z users of TikTok Shop in Indonesia. A quantitative explanatory research design was employed, and data were collected through an online questionnaire administered to 201 eligible respondents selected using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that Fear of Missing Out and Hedonic Shopping Motivation exert positive and statistically significant effects on Impulse Buying. Furthermore, Fear of Missing Out, Hedonic Shopping Motivation, and Impulse Buying each have positive and statistically significant effects on Post-Purchase Dissonance. The mediation analysis also demonstrates that Impulse Buying significantly mediates the relationships between Fear of Missing Out and Post-Purchase Dissonance, as well as between Hedonic Shopping Motivation and Post-Purchase Dissonance. These findings provide empirical support for the Stimulus–Organism–Response (S–O–R) Theory, suggesting that psychological stimuli and hedonic motivation influence consumers' internal states, which subsequently shape behavioral responses manifested in impulsive purchasing and post-purchase regret. This study contributes to the consumer behavior and social commerce literature by offering a comprehensive model that explains the psychological mechanisms underlying post-purchase dissonance among Generation Z consumers. The findings also provide practical implications for digital marketers and businesses operating on social commerce platforms in designing marketing strategies that encourage sustainable consumer satisfaction while minimizing post-purchase regret.